Tidal Pumping Controls Dissolved Organic Matter Properties and Outwelling From Mangrove Groundwater to Coastal Water. Issue 3 (14th March 2023) - Xiao, Kai; Zhang, Peng; Santos, Isaac R.; Wang, Jun‐Jian; Li, Zhenyang; Wang, Xuejing; Wang, Ying‐Hui; Lu, Meiqing; Zhang, Licong; Li, Hailong
Abstract: Dissolved organic matter (DOM) in highly productive intertidal mangroves is an important carbon and nutrient source to the coastal ocean. In highly dynamic mangrove intertidal systems, both tidal pumping or geochemical factors can control DOM characteristics. The influence of groundwater flow on DOM properties and fluxes remains poorly understood. Here, we compared the concentrations, sources, and spectroscopic characteristics of DOM across a recharge‐discharge gradient. We used a three‐dimensional array sampling strategy to reduce spatial biases, groundwater monitoring to quantify tidally driven exchange, and spectrofluoroscopy to quantify DOM fluorescent components. The results showed that tidal hydrology played the key role driving groundwater DOM properties in both horizontal (i.e., from the mangrove to the sea) and vertical directions. Due to the high spatial heterogeneity of dissolved inorganic (DIC) and organic (DOC) carbon concentrations in mangrove groundwater, carbon outwelling showed a high degree of variability at the intertidal scale (54.8–234.8 μmol m −2 d −1 for DIC and 2.5–12.4 μmol m −2 d −1 for DOC). The contribution of terrestrial DOM gradually decreased toward the ocean, but the microbial contributions for recently produced autochthonous DOM increased. Deep groundwater received less terrestrial DOM and experienced anaerobic microbial mineralization, resulting in lower organic carbon than shallow groundwater. Greater variations in spectroscopic characteristics were found in shallow groundwater than in deep groundwater. Overall, tidally driven surface water‐groundwater interactions control the variability in DOM properties and how DOM contributes to carbon budgets and sequestration in mangrove groundwater. Plain Language Summary: Mangroves are carbon‐rich ecosystems producing large amounts of dissolved organic matter (DOM) that can reach the ocean. We conducted detailed groundwater observations to resolve DOM geochemistry along a subtropical mangrove intertidal zone. Tidal flushing of mangrove soils enhanced the exchange between groundwater and surface seawater. Tidal pumping horizontally segmented the intertidal zone into a landward recharge zone of surface water and a seaward discharge zone of groundwater. These zones had contrasting salinity, pH, inorganic carbon, and DOM concentrations and composition. Microbially derived DOM was found in the seaward discharge zone and in deep mangrove groundwater. Deep waters also had higher degree of humification than shallow groundwater. Salinity‐independent humic‐like components were transformed by microbial activity, suggesting external sources. Overall, tidal pumping and the distinct hydrological zones explained DOM chemistry and controlled groundwater‐ocean exchange in mangrove intertidal flats. Key Points: Tidal pumping segmented the intertidal mangrove into a landward recharge zone and a seaward discharge zone 3‐D array sampling reveled high spatial heterogeneity of DOM characteristics Hydrological factors explained DOM‐related variables better than geochemical parameters